Lévi-Strauss e a tríade da estrutura: a linguagem, o simbólico e o inconsciente - Mendes, Tássia Nogueira Eid (2014)
This research had as a goal a better definition of the notion of unconscious in the work of Claude Lévi-Strauss. In the early texts, such as The Symbolic Efficacy (1949), this concept is introduced as a set of structural laws, named Symbolic function. Nevertheless, throughout the path of the levi-straussian work, this terminology fades bit-by-bit, making room for concepts like the symbolic thought. In its turn, this concept imprints the determination of symbolism, characteristic that defines mankind, and thus, the unconscious defines humanity itself. Placed between nature and culture, the unconscious therefore is paradoxically plural and universal, allowing the apprehension of an integrated reality. The pair unconscious/ conscious characterizes the different levels of the phenomenon that Lévi-Strauss analyses in his anthropology, granting two types of investigation: inductive and deductive. The proposal of an unconscious facet of the social phenomenon made possible the prescription of two discontinued methods. The exam of the empirical and transcendental realities is orchestrated in a way of establishing, at the same time, an irreducibly statement between nature and culture and a refusal to old-fashioned dualisms. In this work, throughout the developments of the notion unconscious in the work of Lévi-Strauss, we hope to demonstrate that this concept is symbolic, and that such an analysis implies the investigation of the passage between nature and culture. Therefore, we hope to set the implications of this notion to the definition of mankind in the work of Lévi- Strauss.